Should We Adopt Increased Dilutions for Indirect Immunofluorescence in Pediatric Anti-Centromere Antibody Testing? Insights from a Three-Year Retrospective Study - Mehmet Soylu; Raziye Burcu Taşkın; Gülçin Aytaç; Güzide Aksu; Seyfi Durmaz; Miray Karakoyun; Şaziye Rüçhan Sertöz (Children)
Background/Objectives: Systemic autoimmune rheumatic diseases (SARDs) pose diagnostic challenges, particularly in pediatric populations, due to their diverse presentations and overlapping symptoms. This study aimed to evaluate the diagnostic concordance between indirect immunofluorescence (IIF) at different dilution levels (1/80 and 1/640) and immunoblot findings for anti-centromere antibody (ACA) positivity. Additionally, the clinical significance of ACA positivity and its association with SARDs in pediatric patients was assessed. Methods: This retrospective, cross-sectional study included 58 pediatric patients evaluated for anti-nuclear antibody (ANA) testing at Ege University Hospital from 2019 to 2021. IIF was performed using HEp-20-10 cells and immunoblot testing was conducted to assess CENP-B reactivity. Statistical analyses included chi-square tests, correspondence analysis, and regression modeling to explore the relationship between IIF titers, immunoblot findings, and SARD diagnoses. Results: Among the patients, 62.1% were diagnosed with SARD. Higher IIF titers (≥1/640) were strongly associated with CENP-B 3+ immunoblot positivity, while lower titers (1/80 and 1/320) correlated with CENP-B 1+. Patients with IIF positivity at 1/80 were 15.89 times more likely to have SARD (p < 0.001). Correspondence analysis revealed significant associations between IIF dilution levels and immunoblot reactivity (χ2 = 37.574, p < 0.000). Gender and age were not significant predictors of SARD positivity. Conclusions: This study highlights the diagnostic value of higher IIF dilution levels (≥1/640) in improving ACA detection and SARD diagnosis in pediatric patients. Incorporating complementary diagnostic tools, such as immunoblot testing, can enhance diagnostic accuracy. These findings support adopting higher IIF cutoff levels in clinical practice for pediatric populations.